1999
DOI: 10.1021/jm990371u
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Relative Binding Free Energies of Tacrine−Huperzine A Hybrids as Inhibitors of Acetylcholinesterase§

Abstract: The binding of the 9-methyl derivative of tacrine-huperzine A hybrid to Torpedo californica acetylcholinesterase (AChE) has been studied by computational methods. Molecular dynamics simulations have been performed for the AChE-drug complex considering two different ionization states of the protein and two different orientations of the drug in the binding pocket, which were chosen from a previous screening procedure. Analysis of structural fluctuations and of the pattern of interactions between drug and enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 33 publications
(44 reference statements)
4
60
0
Order By: Relevance
“…Moreover, all of these huprines proved to be much more active than tacrine in reversing the neuromuscular blockade induced by d-tubocurarine. The molecular modeling studies of the complexes of (-)-huprines having a chlorine atom at position 3 and an Et group at position 9 with TcAChE and the Phe330 f Tyr mutated enzyme using the previously proposed model 17,18 are in reasonable agreement with the experimental activity values. Despite the agreement with the experimental data, the definite validation of the binding model has to await a 3D X-ray structure of the complex.…”
Section: Tcachesupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, all of these huprines proved to be much more active than tacrine in reversing the neuromuscular blockade induced by d-tubocurarine. The molecular modeling studies of the complexes of (-)-huprines having a chlorine atom at position 3 and an Et group at position 9 with TcAChE and the Phe330 f Tyr mutated enzyme using the previously proposed model 17,18 are in reasonable agreement with the experimental activity values. Despite the agreement with the experimental data, the definite validation of the binding model has to await a 3D X-ray structure of the complex.…”
Section: Tcachesupporting
confidence: 72%
“…Though the use of a cap of water molecules is an approximate treatment, we adopted it in order to enable comparison of the TI-MD results for chlorine derivatives with those previously reported for related compounds. 18 The system was partitioned into a mobile and a rigid region. The former included the inhibitor, all the protein residues containing at least one atom within 14 Å from the inhibitor, and all the water molecules, while the rest of atoms defined the rigid part.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all AChE inhibitors included in this study possess the same tricyclic tetrahydroacridine-like structure, it is safe to assume that they share with tacrine a common mode of binding to AChE. 30 In fact, the binding mode for huprine derivatives that was anticipated from molecular modeling studies 7,26,27 and later confirmed by the X-ray crystal structure of the AChE-huprine X complex 31 shows that the tetrahydro-9-aminoacridine rings of both tacrine and huprine X appear virtually superimposed when the CR traces of the enzyme in both complexes are overlaid. Furthermore, chlorination at position 6 in tacrine and 1,4-methylenetacrine, or at the equivalent position 3 in dihydroquinazoline and huprine, gives rise in all cases to a significant increase in the inhibitory potencies (Tables 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this choice of inhibitors is particularly well suited for our purposes, because the COMBINE results can be directly contrasted with high-quality information provided by both X-ray crystallographic structures 30,31 and previous free energy calculations. 7,26,27,32 Experimental Data Normalization. IC 50 values for tacrine (Table 1) and dihydroquinazoline (Table 3) derivatives, as well as for the test set of tacrine-related compounds (Table 6), were derived from inhibition of human erythrocyte AChE.…”
Section: Resultsmentioning
confidence: 99%